Sociocultural aspect as a key factor of successful activity - Efimov, Sergey V.; Krylov, Petr M.; Voronina, Marina A.; Kalimullina, Gulzirak H.; Soboleva, Elena V. (Opción, 2019)
The article comprehensively considers indicators of the rural regions’ social development via comparative quantitative research methods. The analysis shows an acceptable level of social development in Europe and a low level of social development in Asia and Latin America, which generally affects the quality of social work, especially in rural regions. The study concludes that online technologies significantly change the social work practice, forming its fundamentally new forms.